Influence of Processing Parameters on Laser Direct Joining of CFRTP and Stainless Steel - Liyuan Sheng; Junke Jiao; Beining Du; Feiya Wang; Qiang Wang (Advances in Materials Science and Engineering)
The CFRTP and the stainless steel were joined by the fiber laser, and the effect of processing parameters on the joint quality was investigated in detail. The heat-affected zone on the stainless steel and the microstructure of the joint interface were examined and analyzed. The results showed that the laser joining process refines the microstructure of the fusion and heat-affected zones in the stainless steel. And the tensile strength of the joint was affected greatly by the laser power and scanning speed but slightly by the clamping pressure. With the PPS additive, the joint shear strength could be improved, and the optimal PPS additive thickness is 300 μm. With the best parameters, joint with a shear strength of 15–17 MPa could be obtained as the laser power is 320–350 W, the scanning speed is 4-5 mm/s, the clamping pressure is about 0.5 Mpa, and the additive PPS thickness is about 300 μm.